Hebrew in the Second Temple period : the Hebrew of the Dead Sea Scrolls and of other contemporary sources : proceedings of the Twelfth International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature and the Fifth International Symposium on the Hebrew of the Dead Sea Scrolls and Ben Sira, jointly sponsored by the Eliezer Ben-Yehuda Center for the Study of the History of the Hebrew Language, 29-31 December, 2008 - Fassberg, Steven Ellis.; Bar-Asher, Mosheh.; Clements, Ruth. (Studies on the Texts of the Desert of Judah, 2013)
The Hebrew of the Dead Sea Scrolls and the book of Ben Sira can be properly understood only in the light of all contemporary Second Temple period sources. With this in mind, 20 experts from Israel, Europe, and the United States convened in Jerusalem in December 2008. These proceedings of the Twelfth Orion Symposium and Fifth International Symposium on the Hebrew of the Dead Sea Scrolls and Ben Sira examine the Hebrew of the Second Temple period as reflected primarily in the Dead Sea Scrolls, the book of Ben Sira, Late Biblical Hebrew, and Mishnaic Hebrew. Additional contemporaneous sources-inscriptions, Greek and Latin transcriptions, and the Samaritan oral and reading traditions of the Pentateuch-are also noted.